A Case Study: the Role of Women in Creating Community on the Dakota Frontier, 1880 to 1920 - (:unkn) unknown (My University, 2015)
ABSTRACT A CASE STUDY: THE ROLE OF WOMEN IN CREATING COMMUNITY ON THE DAKOTA FRONTIER, 1880 TO 1920 by Ruth Page Jones The University of Wisconsin-Milwaukee, 2015 Under the Supervision of Professor Genevieve G. McBride During the Dakota Boom years of 1878 to 1887, Dakota Territory welcomed droves of new families, adding close to 400,000 people in the 1880s. Creating new homes on the treeless prairie, many people faced the challenge of sustaining life without the benefit of an established community. The conditions were too harsh, the weather too unpredictable, and the economy too fragile for anyone to live in isolation. By researching the history of one rural county, Aurora County, from 1880 to 1920, this study examines how women experienced new lives in that area, and how they participated in shaping their societies and developing community. Aurora County was typical of many South Dakota counties east of the Missouri River that were settled during the “boom” era. The rural character of those counties greatly influenced the experiences of the women and the ways in which they shaped their societies. While documenting a new local history, this study also broadens our understanding of women’s lives and their role in building community as they moved onto the South Dakota frontier in the late nineteenth and early twentieth centuries.
Keywords: Community; Dakota; Ladies Aid; Midwest; Pioneer Women; Woman Suffrage